2016
DOI: 10.1080/14728222.2016.1186650
|View full text |Cite
|
Sign up to set email alerts
|

Intraplaque neovascularization as a novel therapeutic target in advanced atherosclerosis

Abstract: Although lack of a valuable animal model of IP neovascularization impeded the investigation of a causal and straightforward link between neovascularization and atherosclerosis, recent evidence shows that vein grafts in ApoE*3 Leiden mice as well as plaques in ApoE(-/-) Fbn1(C1039G+/-) mice are useful models for intraplaque neovessel research. Even though interference with vascular endothelial growth factor (VEGF) signalling has been widely investigated, new therapeutic opportunities have emerged. Cell metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 98 publications
0
27
0
Order By: Relevance
“…Considerable interest is focusing on a treatment approach targeting inhibition of microvessel formation and function within atherosclerotic plaques. Although some antiangiogenic therapies have been tested for atherosclerosis, only limited efficacy was observed (20). In the present study, we investigated a new strategy to treat athrosclerosis by UTMD targeting intraplaque neovascularization in an APOEdeficient mouse model of atherosclerosis.…”
Section: Utmd With Mbie Microbubbles Reduced Expression Of a Marker Omentioning
confidence: 97%
“…Considerable interest is focusing on a treatment approach targeting inhibition of microvessel formation and function within atherosclerotic plaques. Although some antiangiogenic therapies have been tested for atherosclerosis, only limited efficacy was observed (20). In the present study, we investigated a new strategy to treat athrosclerosis by UTMD targeting intraplaque neovascularization in an APOEdeficient mouse model of atherosclerosis.…”
Section: Utmd With Mbie Microbubbles Reduced Expression Of a Marker Omentioning
confidence: 97%
“…5 Uncertainty regarding whether the inhibition of plaque neovessel results in stable plaques remains largely because of the lack of an appropriate plaque-neovessels animal model, which introduces discrepancies in the outcomes of several studies and complicates science-based conclusions. 6 The development of atherosclerotic lesions involves three different pathoanatomic stages of angiogenesis: initiation, progression and complication. Studies of the initiation phase using a rabbit model fed an atherogenic diet for 3 weeks showed that local delivery of bevacizumab (a monoclonal antibody against VEGF-A) inhibited plaque angiogenesis, resulting in smaller atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the initiation phase using a rabbit model fed an atherogenic diet for 3 weeks showed that local delivery of bevacizumab (a monoclonal antibody against VEGF-A) inhibited plaque angiogenesis, resulting in smaller atherosclerotic plaques. 6,7 Despite their clinical relevance, there are few studies of anti-angiogenic therapy on the progression and complication stages and inappropriate anti-angiogenic therapy at these two stages can potentially cause hypoxia and induce endothelial apoptosis, resulting in the loss of integrity of the endothelial vessel lining (bleeding). 8,9 This observation raised concerns regarding the importance of vascular-normalization therapy in atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging need for new therapies to stabilize atherosclerotic lesions. Further understanding of the effects of hypoxia in atherosclerotic lesions could indicate potential therapeutic targets [53,54]. The presence of hypoxia in human carotid atherosclerotic lesions correlates with angiogenesis.…”
Section: Atherosclerosis and Plaque Angiogenesismentioning
confidence: 99%